Visum Et Repertum and Forensic Examination of a Rape Case as a Sexual Crime Towards an Indonesian Migrant Worker in Taiwan - Rizka Rizka1, Wafda Vivid Izziyana2, Arief Budiono2, Heru Santoso Wahito Nugroho3, Sofyan Wimbo Agun (Institute of Medico-legal Publications Pvt Ltd, 2020)
This research aims to describe the forensic examination in the handling of the sexual crime which happened to an Indonesian migrant worker in Taiwan. It is well known that the level of human rights protection in Taiwan is quite good compared that of the other destination countries for migrant workers. Yet, is the good level of human rights protection balanced also with medical treatment or medical forensic examination of the Indonesian migrant worker sexual crime victim who worked in that country. This research uses a nondoctrinal method. This is because the law is not only a normative theory. Yet, it also views the sociological aspects which happen in the society. The research results show that Taiwan is a country with a worrying rate of sexual crime. Yet, it has underwent good procedures in forensic examination, including in visum et repertum and other examinations for sexual assaults which happened to migrant worker victims. The visum et repertum preliminary examination which applies in Taiwan is done through a special unit which is provided for sexual assault victims. The results are acknowledged as evidences of sexual crime. It will be directly coordinated with the Taiwan special unit of justice for sexual crime.